Penanganan kandidiasis orofaring pada pasien Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) dengan nilai CD4 dibawah 10 sel/µL: laporan kasus - Winda Dwi Malinda Masuku; Dian Angriany; Saka Winias; Adiastuti Endah Parmadiati (DiscoverSys Inc., 2021)
Background: The oral manifestation of Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) is an important indicator because it is a disorder that usually appears first when the immune system is suppressed. Oropharyngeal candidiasis is an opportunistic infection that most often occurs in people suffering from HIV infection or AIDS. It is also an important marker in immunosuppressed states with CD4 values below 200 cells/mm3. This case study aims to evaluate the treatment of oropharyngeal candidiasis in patients with HIV/AIDS with CD4 values below 10 cells/µLCase Presentation: A 30-year-old man complained of a thick and uncomfortable feeling in the entire oral cavity felt since 4 months ago. Clinical examination revealed multiple pseudomembranous, which were removed and left a reddish area at the base of most of the oral cavity to the pharynx. The results of the fungal examination showed that the hyphae were not insulated with the results of candida albicans culture, and the absolute CD4 value was 9 cells/µl. On the second visit, the patient admitted that he was HIV positive by bringing a reactive result on the 3-method anti-HIV examination conducted 3 months earlier. This case was handled by administering an antiseptic mouthwash, topical and systemic antifungal, and referred to the IHAN RSUA polyclinic for ARV therapy.Conclusion: The successful treatment of oropharyngeal candidiasis, in this case, depends on integrated therapy between dentists and internists as well as patient compliance in following doctor's instructions. Latar Belakang: Manifestasi oral Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) menjadi indikator penting karena merupakan kelainan yang biasanya muncul pertama kali saat kondisi imun tersupresi. Kandidiasis orofaring merupakan suatu infeksi oportunistik yang paling sering terjadi pada orang yang menderita infeksi HIV atau AIDS. Hal ini juga disadari sebagai suatu pertanda penting pada keadaan imunosupresi dengan nilai CD4 dibawah 200 sel/mm3. Laporan kasus ini bertujuan untuk mengevaluasi penanganan kandidiasis orofaring pada pasien (HIV/AIDS) dengan nilai CD4 dibawah 10 sel/µLPresentasi Kasus: Seorang laki-laki berusia 30 tahun mengeluhkan rasa tebal dan tidak nyaman pada seluruh rongga mulut yang dirasakan sejak 4 bulan yang lalu. Pemeriksaan klinis ditemukan pseudomembran multipel yang dapat dihapus dan meninggalkan area kemerahan di dasarnya pada hampir seluruh rongga mulut hingga ke faring. Hasil pemeriksaan jamur menunjukkan hyphae tidak bersekat dengan hasil biakan candida albicans, dan nilai CD4 absolut 9 cell/µl. Kunjungan kedua Pasien mengakui sebagai pengidap HIV dengan membawa hasil reaktif pada pemeriksaan anti-HIV 3 metode yang telah dilakukan 3 bulan sebelumnya. Penanganan kasus ini dengan pemberian antiseptik kumur, anti jamur topikal dan sistemik serta dirujuk ke poli IHAN RSUA untuk melakukan terapi ARV.Kesimpulan: Keberhasilan penanganan kandidiasis orofaringeal pada kasus ini bergantung pada terapi yang terintegrasi antara dokter gigi dan dokter penyakit dalam serta kepatuhan pasien dalam mengikuti instruksi dokter.